The new morphology of work in Brazil at the 2000’s - Alves, Giovanni (Universidade Estadual Paulista / UNESP, 2011)
The purpose of the text is to expose the elements of the new morphology of organized labor in Brazil, in the sociohistorical context of the reorganization of capitalism. To do so, some indicators of the work market in the last two decades are presented, emphasizing the main characteristics of the process of job insecurity experienced in the country. If the 1990s in Brazil were marked by the growing unemployment and informal employment relations, the decade of 2000, mainly from 2003 on, is mostly known by the flexible nature of employment and work organization, boosted by the scenario of capitalist economy expansion.